2010
DOI: 10.1073/pnas.1016923108
|View full text |Cite
|
Sign up to set email alerts
|

Histone3 lysine4 trimethylation regulated by the facilitates chromatin transcription complex is critical for DNA cleavage in class switch recombination

Abstract: Ig class switch recombination (CSR) requires expression of activation-induced cytidine deaminase (AID) and transcription through target switch (S) regions. Here we show that knockdown of the histone chaperone facilitates chromatin transcription (FACT) completely inhibited S region cleavage and CSR in IgA-switch-inducible CH12F3-2A B cells. FACT knockdown did not reduce AID or S region transcripts but did decrease histone3 lysine4 trimethylation (H3K4me3) at both the Sμ and Sα regions. Because knockdown of FACT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
143
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(155 citation statements)
references
References 37 publications
12
143
0
Order By: Relevance
“…As shown in Fig. 4A, the SSRP1 knockdown did not alter the H3.3 deposition levels in the V(D)J and Sμ regions, but it reduced the H3K4me3 occupancy, in agreement with our previous findings in SSRP1-depleted murine B lymphoma cells (16), indicating that FACT is not required for H3.3 deposition into Igh chromatin.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…As shown in Fig. 4A, the SSRP1 knockdown did not alter the H3.3 deposition levels in the V(D)J and Sμ regions, but it reduced the H3K4me3 occupancy, in agreement with our previous findings in SSRP1-depleted murine B lymphoma cells (16), indicating that FACT is not required for H3.3 deposition into Igh chromatin.…”
Section: Resultssupporting
confidence: 91%
“…We previously reported that H3K4me3 serves as a marker for SHM and CSR (5,16). In CSR, FACT contributes to the DNA break by promoting the trimethylation of H3K4 (16). Regarding SHM, we reported that H3K4me3 is enriched in SHM target regions (5).…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Location of breakpoints in S 1 implicated in the targeting of the CSR machinery (including AID and RNA Pol II) to S regions primed for CSR [25][26][27][28] . Altogether with DNA transcription, this remodelling of chromatin in S regions constitutes a hallmark of the accessibility to CSR factors.…”
Section: ′Rr-deficientmentioning
confidence: 99%